Videolaryngoscopy versus direct laryngoscopy for emergency orotracheal intubation outside the operating room: a systematic review and meta-analysis. (April 2018) - Arulkumaran, N.; Lowe, J.; Ions, R.; Ruano, M.M.; Bennett, V.; Dunser, M.W.
Abstract: Videolaryngoscopy (VL) may improve the success of orotracheal intubation compared with direct laryngoscopy (DL). We performed a systematic search of PubMed, Embase, and CENTRAL databases for studies comparing VL and DL for emergency orotracheal intubations outside the operating room. The primary outcome was rate of first-pass intubation, with subgroup analyses by location, device used, clinician experience, and clinical scenario. The secondary outcome was complication rates. Data are presented as [odds ratio (95% confidence intervals); P -values]. We identified 32 studies with 15 064 emergency intubations. There was no difference in first-pass intubation with VL compared with DL [OR=1.28, (0.99–1.65); P =0.06]. First-pass intubations were increased with VL compared with DL in the intensive care unit (ICU) [2.02 (1.43–2.85); P <0.001], and similar in the emergency department or pre-hospital setting. First-pass intubations were similar with GlideScope ®, but improved with the CMAC ® [1.32 (1.08–1.62); P =0.007] compared with DL. There was greater first-pass intubation with VL compared with DL amongst novice/trainee clinicians [OR=1.95 (1.45–2.64); P <0.001], but not amongst experienced clinicians or paramedics/nurses. There was no difference in first-pass intubation with VL compared with DL during cardiopulmonary resuscitation or trauma. VL compared with DL was associated with fewer oesophageal intubations [OR=0.32 (0.14–0.70); P =0.003], but more arterial hypotension [OR=1.49 (1.00–2.23); P =0.05]. In summary, VL compared with DL is associated with greater first-pass emergency intubation in the ICU and amongst less experienced clinicians, and reduces oesophageal intubations. However, VL is associated with greater incidence of arterial hypotension. Further trials investigating the utility of VL over DL in specific situations are required.